Radial force control of multi-sector permanent magnet machines - Valente, Giorgio; Papini, Luca; Formentini, Andrea; Gerada, C.; Zanchetta, Pericle (2016)
The paper presents an alternative radial force control technique for a Multi-Sector Permanent Magnet machine (MSPM). Radial force control has been widely investigated for a variety of bearingless machines and can be also applied to conventional PMSM aiming the reduction of the mechanical stress on the bearings as well as reduce the overall vibration. Traditional bearingless motors rely on two independent sets of windings dedicated to torque and suspension respectively. The work presented in this paper takes advantage of the spatial distribution of the winding sets within the stator structure towards achieving a controllable net radial force. In this paper the α-β axis model for the MSPM and the theoretical investigation of the force production principle is presented. A novel force control methodology based on the Single Value Decomposition (SVD) technique is described. The predicted performances of the MSPM have been validated using Finite Element simulations and benchmarked against state of the art control techniques.